Factors associated with cesarean delivery in a Peruvian Hospital - Sinchitullo Castillo, Angel Eduardo (2020)
Introduction: Caesarean sections carry maternal and perinatal risks. Objective: To determine thefactors associated with cesarean delivery in patients treated in the gynecology obstetrics service atthe Hospital Militar Central, in the 2014-2018 period. Methods: Analytical, retrospective, case-controlstudy; the population was vaginal or caesarean deliveries attended during the years 2014 to 2018. Thesampling was systematic, and the sample size was 988 deliveries of which 329 were caesarean sections.Chi-square and logistic regression tests were applied to calculate the odds ratio; The analysis was carriedout with the statistical program SPSS 23. Results: In pregnant women, previous caesarean section wasa factor associated with caesarean section (OR = 1.55, 95% CI = 1.12-2.15); neither age, gestational age,nor prenatal controls were a factor associated with caesarean section (p>0.05). Educational level wasalso not a factor associated with caesarean section, but the number of children was (OR = 0.83, 95% CI =0.72-0.95). Conclusion: Having previous caesarean sections, few children, an older age, were significantrisk factors for cesarean delivery.